QUALITY OF LIFE OF FARMERS IN THE SOUTHERN REGION: RUBBER PLANTERS IN NAKHON SI THAMMARAT PROVINCE - หมัดอ่าดัม, พีรดาว (Thai Interdisciplinary and Sustainability Review, 2023)
This research’s objectives were to study the quality of life of rubber farmers and comparative analysis of gender, age, education, income factors affecting quality of life of rubber farmers. The research instrument was a questionnaire, data were collected from a sample of 384 people and the statistic used for analysis was percentage, mean, standard deviation, t-test and F-test. The results of this study ​​showed that the quality of life of rubber farmers is moderate. When considering each aspect, it was found that spiritual and family at a high-level health and functional section and social and economic at a low level when analyzing personal factors found that the sexes are different, and the level of education had no difference in the overall quality of life. Different ages had a statistically significant difference in health and function at the .05 level, the socioeconomic aspect was statistically different at the .05 level and the family aspect was significantly different statistically at .05 level and spiritual no different income affect the quality of life differently. When considering each aspect, it was found that the health and function were significantly different at the .05 level, the socio-economic aspect was significantly different at the .05 level. no different